2008
DOI: 10.2337/db06-1755
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Diabetes in Hemizygous Human Amylin Transgenic Mice That Developed Neither Islet Amyloid nor Peripheral Insulin Resistance

Abstract: OBJECTIVES-We sought to 1) Determine whether solublemisfolded amylin or insoluble-fibrillar amylin may cause or result from diabetes in human amylin transgenic mice and 2) determine the role, if any, that insulin resistance might play in these processes.RESEARCH DESIGN AND METHODS-We characterized the phenotypes of independent transgenic mouse lines that display pancreas-specific expression of human amylin or a nonaggregating homolog, [ 25,28,29 Pro]human amylin, in an FVB/n background.RESULTS-Diabetes occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
6
37
0
1
Order By: Relevance
“…It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l). Recent studies using transgenic rodents have demonstrated that endoplasmic reticulum (ER) stress caused by formation of intracellular hIAPP fibrils [30,31] and oxidative stress [32] also contribute to cytotoxic effects of hIAPP.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l). Recent studies using transgenic rodents have demonstrated that endoplasmic reticulum (ER) stress caused by formation of intracellular hIAPP fibrils [30,31] and oxidative stress [32] also contribute to cytotoxic effects of hIAPP.…”
Section: Introductionmentioning
confidence: 99%
“…Because the major difference in body weight between amylin knockout and wild-type mice occurred mainly within the first 3 to 4 months of life, the same may also hold true for animals overexpressing amylin. Another recent article with mice that were transgenic for the overexpression of human amylin did not report data on eating and body weight (Wong et al, 2008).…”
Section: A Genetic Models Of Amylin Deficiency or Overexpressionmentioning
confidence: 99%
“…On the other hand, extracellular amyloid peptides have been shown to trigger CD95 (FAS) death receptor signalling [18] and elicit suicidal cell death or apoptosis of pancreatic ß-cells [12,13,[19][20][21][22][23][24][25][26][27][28][29] fostering the development of diabetes mellitus [1,[30][31][32]. Accordingly, diabetes develops in hemizygous human amylin transgenic mice [33]. Conversely, suppression of proislet amyloid polypeptide enhances survival of pancreatic islet cells [34].…”
Section: Introductionmentioning
confidence: 97%